2013
DOI: 10.1063/1.4809727
|View full text |Cite
|
Sign up to set email alerts
|

Mobility enhancement in amorphous InGaZnO thin-film transistors by Ar plasma treatment

Abstract: The effects of Ar plasma treatment on the back-channel of amorphous InGaZnO (a-IGZO) thin-film transistors are investigated. A decrease in metallic ion-oxygen bonding in the Ar plasma-treated a-IGZO channel layer was observed by X-ray photoelectron spectroscopy (XPS) depth profile analysis. An increase in the channel charge carrier concentration is estimated from the increased oxygen vacancy atomic ratio using XPS curve decomposition analysis. The plasma-treated area of the a-IGZO back-channel is varied with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 13 publications
3
28
1
Order By: Relevance
“…The decrease in the intensity can be explained by the passivation of oxygen vacancy sites with ambient hydrogen/water molecules, consistent with the reported in [23]. The existence of hydrogen is usually confirmed by the oxidized (−OH) subband at the binding energies of ∼532.3 eV in the O 1s spectrum [24], but our experimental evidence indicates the reduction in intensity of both the oxygen vacancy (531.55 eV) and the −OH (532.3 eV), after the incorporation of hydrogen/water molecules. In Fig.…”
supporting
confidence: 87%
“…The decrease in the intensity can be explained by the passivation of oxygen vacancy sites with ambient hydrogen/water molecules, consistent with the reported in [23]. The existence of hydrogen is usually confirmed by the oxidized (−OH) subband at the binding energies of ∼532.3 eV in the O 1s spectrum [24], but our experimental evidence indicates the reduction in intensity of both the oxygen vacancy (531.55 eV) and the −OH (532.3 eV), after the incorporation of hydrogen/water molecules. In Fig.…”
supporting
confidence: 87%
“…The crystal structure of plasma treated AZO and TZO films did not change considerably, but the resistivity of plasma treated films decreased significantly. Various plasma surface treatment, such as N 2 O [15], N 2 , SiH 4 , NH 3 [16], Ar [17], H 2 [18], have remarkable effects on the structural, optical and electrical properties of InGaZnO 4 (IGZO) films. It is recently found that the He plasma treatment is also an effective method to improve the conductivity of IGZO films [19].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the electron detrapping rate and the decreasing rate of ∆V th is not sensitive to V Stress . (oxygen-metal bonding, -O-M), the oxygen vacancies (V O ) and the weakly bound oxygen species on the a-IGZO surface (such as -O-H), respectively [16]. It is seen that after 60-s N 2 O plasma treatment, the intensity of the O I peak increases from 46.78% to 51.06%, and the intensity of the O II peak decreases from 30.19% to 27.92%.…”
Section: Methodsmentioning
confidence: 99%